Comunicação para a Sustentabilidade: Garimpando Educomunicação Socioambiental na Chapada Diamantina (BA) - Novais Filho, Diosvaldo Pereira (2024)
“Communication for Sustainability: Searching for Socio-environmental Educommunication in Chapada Diamantina” is inspired by the creation, developments and content analysis of TV UNEB-Seabra. This University TV, linked to Campus XXIII of the State University of Bahia, in Seabra, in Chapada Diamantina BA, was born amid the pandemic caused by COVID-19 and becomes an important alternative means of communication for the Chapada Diamantina Identity Territory . All content production, previously linked only to responding to the University's demands, began to broadcast programs, series and lives with different agendas, produced by the region's residents themselves, who previously did not see themselves included in the information conveyed in the traditional media, the mass media. average. Given this reality, and realizing the proximity of this audiovisual production to what Environmental Education advocates in its critical perspective, Educommunication and Socio-Environmental Educommunication, we aim to show a portrait of the use of these pedagogical-theoretical-practical practices in the production of content present on TV UNEB-Seabra and, in parallel, verify the presence of projects in the Territory that cover these areas of knowledge. This research was carried out with a qualitative-quantitative perspective, based on Content and Network Analysis for Social Media, since TV Universitária is on a Social Network platform, YouTube. To collect data relating to the projects, a scan was carried out on internet search engines and direct contact was made with the Education Departments of the municipalities that make up the Chapada Diamantina Territory. To assist in the proposed discussions, a literature review and analysis of documentary materials were carried out. The following educational products were produced: “Map of Educommunication in the Identity Territory of Chapada Diamantina” and the construction of “Actions in Socio-environmental Educommunication contextualized in Chapada Diamantina”. The results presented show us the proximity of Environmental Education with Educommunicative practice and highlights audiovisual production, through alternative media, as an ally to guide themes related to Environmental Sciences.